Discovery of Actinomycetes from Extreme Environments with Potential to Produce Novel Antibiotics - Trenozhnikova, Lyudmila; Azizan, Azliyati (University of Pittsburgh, University Library System, 2018)
Introduction: Antimicrobial-resistant pathogens pose serious challenges to healthcare institutions and health of the public. Thus, there is an urgent need for the discovery of new and effective antimicrobial agents. Microorganisms that exist in extreme environments such as those with high salinity or alkalinity, are known as extremophiles, and include various species of actinomycetes. The goal of this study is to discover novel antibiotics from extremophiles found in Kazakhstan that are effective against drug resistant pathogens. Methods: Soil from extreme environments of Kazakhstan was collected, and pure cultures of actinomycetes were isolated and cultured in modified Bennett’s broth with either high concentrations of salt or high pH to mimic extreme environments. Extracts obtained from selected actinomycetes strains were used to test for antimicrobial activity against Staphylococcus aureus, Escherichia coli and Aspergillus niger. Results: A total of 5936 strains of extremophile actinomycetes were isolated; from these, 2019 strains were further isolated into pure cultures. Of these, 415 actinomycetes strains that demonstrated antagonistic antibacterial activities were selected. These actinomycetes were further classified into groups and subgroups based on their responses to different culture conditions. Antimicrobial antagonism activity for some of the actinomycetes strains was dependent on culture conditions and development of aerial mycelia under extreme conditions. Conclusion: We identified several interesting candidate extracts with putative antimicrobial activities against several strains of drug resistant pathogens. Our research of the actinomycetes’ ability to produce antibiotics in the near-natural conditions provides a great opportunity to assess their biodiversity and distribution in the Central Asian region and to develop new methodological approaches to the screening of new antimicrobial agents.
http://cajgh.pitt.edu/ojs/index.php/cajgh/article/view/337
Keywords: actinomycetes; antibiotics; pathogens; antibiotic resistance; pathogens; natural products; extremophiles